Adjuvant physical exercise for the management of painful polyneuropathy. Issue 5 (4th July 2022) - Liampas, Andreas; Hadjigeorgiou, Loizos; Nteveros, Antonios; Ioannou, Christiana; Varrassi, Giustino; Zis, Panagiotis
ABSTRACT: Introduction: Physical exercise appeared to be effective, when implemented as an adjuvant to the pharmacotherapy option, in a variety of painful conditions. Peripheral neuropathic pain (PNP) is very prevalent and affects up to two-thirds of individuals with polyneuropathy (PN), regardless of etiology. The aim of this systematic review was to evaluate the currently available studies that assess adjuvant physical exercise for the management of PNP. Methods: A systematic literature search was conducted in the PubMed international database. For the systematic search, three medical subject headings (MeSH) were used. Term A was 'physical exercise' OR 'exercise' OR 'activity' OR 'workout' OR 'training'; term B was 'pain' OR 'painful'; term C was 'neuropathy' OR 'polyneuropathy.' Additionally, three filters were used: human subjects, English language, and full text. The reference lists of eligible papers and relevant reviews were also meticulously searched in order to include further relevant studies. Six papers eligible to be included were identified. Results: Physical exercise in various forms can be of benefit in the management of PNP when used as an adjuvant to the standard care. Overall, using the American Society of Interventional Pain Physicians (ASIPP) criteria, the current best available evidence exists for both aerobic and muscle strengthening exercise programs (level II evidence). The intensity of the exercise seems to play a significant role, with higher intensity interval training programs being more promising, though this remains to be confirmed in future studies. Conclusions: Physical exercise is a promising non-pharmacological intervention for the management of PNP. Future RCTs should be conducted to make a face-to-face comparison of the available exercise treatments with the aim to design specific exercise programs for patients with PNP.